ANALISIS KEMANDIRIAN FISKAL DAN KETERGANTUNGAN FISKAL DI PROVINSI NTB PRIODE 2019-2023 - Lale Ria Aryan (Nusantara Hasana Journal, 2026)
This study analyzes the dynamics of fiscal independence and fiscal dependence in West Nusa Tenggara (NTB) Province during the 2019–2023 period within a fiscal decentralization framework that requires local governments to strengthen their own revenue capacity while simultaneously managing the dominance of intergovernmental transfers. The study focuses on a more comprehensive understanding of changes in the regional revenue structure through three commonly used financial performance indicators: the Regional Independence Ratio (RKD), the Degree of Fiscal Decentralization (DDF), and the Transfer Dependence Ratio. Unlike descriptive ratio studies that tend to focus on a single indicator or ignore the financing component, this study emphasizes the RKD, which includes loans as a comparative measure (transfers + loans) to avoid biased interpretations of independence due to the use of short-term financing. The method used is a descriptive quantitative approach based on data processing from the NTB Provincial Government's Budget Realization Report/LKPD for 2019–2023. The analysis is conducted by calculating annual trends in the three ratios and interpreting changes in the central-regional relationship pattern using the RKD intervals (instructive, consultative, participatory, and delegative). This approach allows for a simultaneous understanding of strengthening Locally-Owned Revenue (PAD), changes in the portion of transfers, and the role of loans in shaping regional fiscal space. The results indicate an improvement in NTB's internal fiscal capacity during the observation period. The Regional Original Revenue (RKD) increased from 49.58% (2019) to 92.76% (2023), indicating that financing is increasingly supported by PAD. The Regional Debt-to-Debt (DDF) also increased from 33.15% to 48.12%, indicating a larger contribution of PAD to total revenue (PAD + transfers), although it has not yet exceeded the 50% threshold. Correspondingly, the dependency ratio decreased from 66.85% (2019) to 51.88% (2023), indicating a weakening of transfer dominance and a shift toward a more balanced revenue structure. However, annual dynamics show that changes are not always linear; in 2021, the RKD decreased slightly despite an increase in PAD due to loans increasing the denominator (transfers + loans), while the 2023 spike was relatively analytically "clean" because loans were zero. Interpretatively, NTB shifted from a consultative model (2019) to a participatory one (2020–2022) and then to a delegative one (2023). This finding underscores the urgency of strengthening the regional original revenue (PAD) base through continuous intensification and extensification, while managing transfer dependence as a fiscal risk to changes in regional allocation (TKDD) policies. The novelty of this research lies in the integration of three ratios within the provincial locus, emphasizing the role of loans in reading the Regional Budget (RKD), and linking ratio trends to central-regional relationship patterns to enrich policy implications.